Redescription of immatures of Dasyhelea flavifrons Guérin-Méneville (Culicomorpha: Ceratopogonidae) and new contribution to the knowledge of its larval habitats - Díaz, Florentina (2019)
The fourth instar larva and pupa of Dasyhelea flavifrons Guerin-Meneville are redescribed, illustrated, and photomicrographed using binocular, phase-contrast, and scanning electron microscopy. Comparisons with the American species of the grisea group were made. The immatures were collected by using a siphon bottle in tree-holes and from water collected in dead snail shells in Salta Province, Argentina, transported to the laboratory and there bred to the emergence of the adults. Details on larval habitats are given. These are the first records from Argentina and in gastrotelmata.